2016
DOI: 10.1111/sifp.12006
|View full text |Cite|
|
Sign up to set email alerts
|

Family Planning Vouchers in Low and Middle Income Countries: A Systematic Review

Abstract: Family planning (FP) vouchers have targeted subsidies to disadvantaged populations for quality reproductive health services since the 1960s. To summarize the effect of FP voucher programs in low‐ and middle‐income countries, a systematic review was conducted, screening studies from 33 databases through three phases: keyword search, title and abstract review, and full text review. Sixteen articles were selected including randomized control trials, controlled before‐and‐after, interrupted time series analyses, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 51 publications
1
54
0
Order By: Relevance
“…Although our study does not show that access of BTL and vasectomy can be attributed to voucher scheme, it still reveal that more OBA clients than non-OBA clients are using the two methods. Nevertheless, the finding is consistent with other literature that shows that demand side financing improves uptake of services [25, 26, 32]. The results could be attributed to the fact that the voucher service distributers (VSDs) have also been used to cover areas that were considered long distance from the facilities which aided in eliminating the obstacles to utilizing the methods in addition to explaining the benefits of long acting and permanent family planning methods [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although our study does not show that access of BTL and vasectomy can be attributed to voucher scheme, it still reveal that more OBA clients than non-OBA clients are using the two methods. Nevertheless, the finding is consistent with other literature that shows that demand side financing improves uptake of services [25, 26, 32]. The results could be attributed to the fact that the voucher service distributers (VSDs) have also been used to cover areas that were considered long distance from the facilities which aided in eliminating the obstacles to utilizing the methods in addition to explaining the benefits of long acting and permanent family planning methods [31].…”
Section: Discussionsupporting
confidence: 89%
“…One of the key goals of the voucher management system is to increase access and utilization of long term family planning (LTFP) methods [11, 20, 23, 2629] and; thus, this paper evaluated access of LTFP methods by the women of reproductive age in the voucher scheme or OBA program in Kenya. One major finding is that there are two time more OBA clients who have utilized LTFP methods as compared to non-OBA clients within the OBA facilities.…”
Section: Discussionmentioning
confidence: 99%
“…), including all interventions involving payment for performance that have a supply‐side component; and (v) social protection programs that provided a voucher (Bellows et al. ) subsidy to disadvantaged clients and reimbursed healthcare workers for providing contraceptive services at a pre‐defined quality standard, including referral vouchers. Social marketing and franchising were not included as these were examined by other recent systematic reviews (Sweat et al.…”
Section: Methodsmentioning
confidence: 99%
“…Five intervention groups were identified, and for each a specific systematic review was carried out. The specific interventions groups were: (i) introduction of community financing and community-based health insurance (Karra et al 2016), which included interventions for family planning that focus on the role of the community in mobilizing, pooling, and allocating reproductive health resources through various health financing instruments, including micro-insurance, microfinance and microcredit, mutual health organizations, and community-managed user fees; (ii) introduction of conditional and unconditional cash transfers (Khan et al 2016); (iii) introducing, removing, or changing out-of-pocket payments or user fees (Korachais et al 2016); (iv) results-based financing (Blacklock et al 2016), including all interventions involving payment for performance that have a supply-side component; and (v) social protection programs that provided a voucher (Bellows et al 2016) subsidy to disadvantaged clients and reimbursed healthcare workers for providing contraceptive services at a pre-defined quality standard, including referral vouchers. Social marketing and franchising were not included as these were examined by other recent systematic reviews (Sweat et al 2012;Westley and Shochet 2013).…”
Section: Interventionsmentioning
confidence: 99%
“…• This has included systematic reviews of specific financing models (and their effective inclusion of FP), such as community financing and community-based health insurance (Karra et al, 2016), conditional and unconditional cash transfers (Khan et al, 2016), introducing, removing, or changing OOP or user fees (Korachais et al, 2016), results-based financing (Blacklock et al, 2016), performance-based incentives (Bellows et al, 2014), and social protection programs that provide a voucher subsidy (Bellows et al, 2016). A summary of the systematic reviews concluded that there is 'limited scientific evidence on the effectiveness of the various financing mechanisms for contraception' and that more robust studies are required (Lissner and Ali, 2016).…”
Section: Section 2 Health Financing and Family Planningmentioning
confidence: 99%